The History of Lentil (Lens culinaris subsp. culinaris) Domestication and Spread as Revealed by Genotyping-by-Sequencing of Wild and Landrace Accessions - Liber, Marta; Duarte, Isabel; Maia, Ana Teresa; Oliveira, Hugo R. (Frontiers in Plant Science, 2021)
Protein-rich legumes accompanied carbohydrate-rich cereals since the beginning of agriculture and yet their domestication history has been scarcely investigated. Lentil (Lens culinaris Medik. subsp. culinaris) was first cultivated in Southwest Asia 10,000-8,000 years ago but archaeological evidence is unclear as to how many times it was independently domesticated, in which region(s) and whether wild species within the Lens genus contributed to the cultivated gene pool. In this study we combined genotyping-by-sequencing (GBS) of 190 accessions from wild (67) and domesticated (123) lentils from the Old World with archaeological information to explore the evolutionary history, diffusion, and adaptation of lentils to different environments. GBS identified 87,647 single nucleotide polymorphisms (SNPs) which allowed a phylogenetic reconstruction of the Lens genus. We confirmed previous studies proposing four groups within it. The only inter-taxa gene flow detected was between cultivated lentil and its progenitor (Lens culinaris subsp. orientalis) albeit at very low levels. Nevertheless, a few hybrids or feral accessions were identified. Within cultivated lentil we found three populations, each with a predominant geographical distribution. Phylogenetics, population structure and archaeological data coincide in a scenario of protracted domestication of lentils, with two domesticated gene pools emerging in Southwest Asia. Admixed varieties are found throughout the species range suggesting a relaxed selection process. A small number of alleles involved in domestication and adaptation to climatic variables were identified. Both novel mutation and selection on standing variation are presumed to have played a role in lentil’s adaptation to different environments. The results presented have implications for understanding the process of plant domestication (past), the distribution of genetic diversity in germplasm collections (present), and for targeting genes in breeding programs (future).